Edukasi tentang HIV/AIDS pada Siswa SMA Negeri 1 Ternate - Liasari Armaijn; Dewi Darmayanti (Jurnal Surya Masyarakat, 2024)
Human Immunodeficiency Virus (HIV) was a virus who infected white blood cells caused human immune system deficiency. Acquired Immune Deficiency Syndrome (AIDS) was a disease with syndrome caused by Immunodeficiency Virus (HIV). Even fluctuative but Indonesian data of HIV/AIDS keep increase every year. In the past eleven years, cases of HIV in Indonesia been in the highest cases at 2019 with 50.282 cases. In North Maluku, new cases of HIV/AIDS on September become 140 cases and cumulative data was 1.325 cases. In Ternate, there were 641 cases of HIV/AIDS which 135 people died. Data shows that HIV/AIDS cases increase on household and productive ages. If the incubation of HIV/AIDS was 8-10 years than infection must be on school ages. Therefore, education on school period become a determinant factor to prevent HIV/AIDS.